Lipopolysaccharide-induced chronic inflammation increases female serum gonadotropins and shifts the pituitary transcriptomic landscape - Garcia, Christopher; Velez, Leandro M.; Ujagar, Naveena; Del Mundo, Zena; Nguyen, Thu; Fox, Chelsea; Mark, Adam; Fisch, Kathleen M.; Lawson, Mark A.; Duleba, Antoni J.; Seldin, Marcus M.; Nicholas, Dequina A. (Frontiers in Endocrinology, 2024)
Female reproductive function depends on a choreographed sequence of hormonal secretion and action, where specific stresses such as inflammation exert profound disruptions. Specifically, acute LPS-induced inflammation inhibits gonadotropin production and secretion from the pituitary, thereby impacting the downstream production of sex hormones. These outcomes have only been observed in acute inflammatory stress and little is known about the mechanisms by which chronic inflammation affects reproduction. In this study we seek to understand the chronic effects of LPS on pituitary function and consequent luteinizing and follicle stimulating hormone secretion. A chronic inflammatory state was induced in female mice by twice weekly injections with LPS over 6 weeks. Surprisingly, serum luteinizing and follicle stimulating hormone was not inhibited and instead we found it was increased with repeated LPS treatments. Here, analysis of bulk RNA-sequencing of murine pituitary revealed paracrine activation of TGFβ pathways as a potential mechanism regulating FSH secretion in response to chronic LPS. These results provide a framework with which to begin dissecting the impacts of chronic inflammation on reproductive physiology.